Potato starch production side stream is a suitable medium for microalgae cultivation - Šupraha, Luka; Costa, Margarida; Dale, Trine; Kahala, Minna; Joutsjoki, Vesa; Pihlanto, Anne; Wood, Ethan; Li, Yan (Elsevier, 2025)
Agro-industrial side streams can provide alternative substrates for microalgae cultivation and sustainable production of valuable bioproducts through recycling and re-use of limited resources. This work explored the potential for using a side stream from potato starch production (evaporation-concentrated potato cell fluid, potato juice) as an alternative medium for scaled-up cultivation of microalgae. A high-throughput screening approach was employed to identify strains of green algae that can grow in the side stream. The selected candidate strains were tested further in optimization experiments to determine the suitable side stream concentration and optimal light intensity. Finally, two strains with the highest specific growth rates in the side stream, Chlorella sp. (NIVA-CHL 15) and Chlorococcum sp. (NIVA-CHL 103) were cultivated in 3 L flat-panel photobioreactors. The biomass was harvested and assessed for the content of carotenoids, fatty acids and amino acids. The 1 % potato juice medium supported growth rates and biomass yield comparable to the commercial algal media, with similar biochemical profiles of the harvested biomass. These results demonstrate that microalgae biotechnology can be employed to valorise unexploited side streams from potato starch production, adding a circular value to this agro-industrial process.
Keywords: potato juice; microalgae; high-throughput screening; carotenoids; amino-acids; fatty-acids